Pengaruh Daya Tarik Brand Ambassador Dan Tingkat Pengetahuan Pesan Iklan Head & Shoulders Terhadap Minat Beli Produk Head & Shoulders - Fitriyani, Putri; Nur Suryanto Gono, Joyo; Pradekso, Tandiyo (Interaksi Online, 2024)
Head & Shoulders, as one of the well-known shampoo brands in Indonesia, become trending topics & viral among netizens but do not show an increase in product sales. Despite various communication strategies, including creating attractive advertisements and collaborating with two brand ambassadors, Joe Taslim and Fadil Jaidi. This research aims to determine the influence of brand ambassador attractiveness and the advertising message knowledge level of Head & Shoulders on the purchase interest in Head & Shoulders products. The theories used in this study are the Source Attractiveness Theory and Advertising Exposure Theory. The sample size in this study was 100 people aged 20-29 who had seen the Head & Shoulders ad titled “Joe Taslim X Fadil Jaidi – Who Is the Next Head & Shoulders BA?” and were domiciled in Semarang. The sampling technique used in this study was non-probability sampling with a purposive sampling method approach. The results showed that the influence of the brand ambassador attractiveness variable on the Head & Shoulders product purchase interest variable obtained a significance value of <0,001, where this number is smaller than 0,01, which means highly significant, indicating the influence of brand ambassador attractiveness on the purchase interest in Head & Shoulders products. Likewise, the variable of the advertising message knowledge level of Head & Shoulders on the variable of the purchase interest in Head & Shoulders products obtained a significance value of <0,001, where this number is smaller than 0,01, which means highly significant, indicating the influence of the advertising message knowledge level of Head & Shoulders on the purchase interest in Head & Shoulders products.